Pengaruh Lingkungan Fisik Terhadap Keputusan Berkunjung Wisatawan Ke Desa Wisata Pulau Semambu Kabupaten Ogan Ilir - Rahmahtika Fadillah; Heri Setiawan; Rini Rini (Politeknik Negeri Sriwijaya, 2021)
This study aims to determine the effect of the Physical Environment on Visiting Decisions. This study uses descriptive quantitative research methods with data collection techniques in the form of survey techniques to visitors who have come or visited Semambu Island Tourism Village through interviews, questionnaires, and documentation, this study uses incidental sampling technique with a sample of 70 respondents. The research data uses Simple Linear Regression Analysis processed with IBM SPSS Ver 25. The results show that the physical environment and tourist attractions have a positive relationship and have a significant effect on visiting decisions.